Worldwide diversity of endophytic fungi and insects associated with dormant tree twigs - Franic, Iva (2022)
International trade in plants and climate change are two of the main factors causing damaging tree pests (i.e. fungi and insects) to spread into new areas. To mitigate these risks, a large-scale assessment of tree-associated fungi and insects is needed. We present records of endophytic fungi and insects in twigs of 17 angiosperm and gymnosperm genera, from 51 locations in 32 countries worldwide. Endophytic fungi were characterized by highthroughput sequencing of 352 samples from 145 tree species in 28 countries. Insects were reared from 227 samples of 109 tree species in 18 countries and sorted into taxonomic orders and feeding guilds. Herbivorous insects were grouped into morphospecies and were identified using molecular and morphological approaches. This dataset reveals the diversity of tree-associated taxa, as it contains 12,721 fungal Amplicon Sequence Variants and 208 herbivorous insect morphospecies, sampled across broad geographic and climatic gradients and for many tree species. This dataset will facilitate applied and fundamental studies on the distribution of fungal endophytes and insects in trees.